Pengembangan Mikroskop Digital Berbasis Blended Learning untuk Meningkatkan Kecerdasan Jasmaniah Kinestetik Mahasiswa pada Praktikum Anatomi Tumbuhan - Sugianto Sugianto; Any Fitriani; Sri Anggraeni; Wawan Setiawan (Jurnal Inovasi Pendidikan dan Sains, 2020)
The initial conditions of learning the practice of plant anatomy at the University of Wiralodra shows that the kinesthetic physical intelligence of students has not been trained. It is proven that students do not feel trained in operating the microscope and determine the magnification of the microscope, which means that the kinesthetic physical intelligence of students has not been trained. Based on these problems, a digital microscope is needed that can train students' kinesthetic physical intelligence in practicing plant anatomy. Digital microscope technology innovation is needed as a means of supporting plant anatomy practicum. In accordance with the nature of the research is the development of a digital microscope based on blended learning, the type used in this research is Research and Development (Research and Development). The trial subjects in this study were prospective biology education teacher candidates in the 2nd semester of Biology Education study program at the University of Wiralodra consisting of 5 classes and totaling 185 students. Sampling using cluster random sample method, consisting of 2 classes, namely Bio B (experimental class) and Bio D (control class) provided that the population is homogeneous. The results of the development of a digital microscope based on blended learning used in plant anatomy practicums were declared very valid. The blended learning digital microscope that was developed can improve the kinesthetic physical intelligence of students in plant anatomy practices, in the high category. There is a significant difference in the increase in kinesthetic physical intelligence of students between classes that use a digital microscope based on blended learning and classes that use a binocular light microscope.